Pole piece and preparation method thereof, battery and energy storage device

By using active material layer and sheet-like porous carbon material on the secondary battery electrode sheet, combined with sintering treatment technology, the problem of high resistivity of the electrode sheet is solved, the rate performance and cycling performance are improved, and it is suitable for high-demand energy storage applications.

CN119481060APending Publication Date: 2025-02-18XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411603810.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The resistivity of existing secondary battery poles is high, resulting in poor rate performance and cycling performance, especially in wind power generation energy storage and solar power generation energy storage scenarios.

Method used

The electrode sheet using a current collector, wherein at least one side has an active material layer, and the active material particles are distributed with a sheet-like porous carbon material. The sheet-like porous carbon material is partially formed from a carbon-containing precursor material with a carbonization temperature range of 150°C to 400°C. It forms after carbonization. The electrode sheet reduces resistivity and improves conductivity by sintering.

Benefits of technology

By reducing the resistivity of the electrode plate, the rate performance and cycle performance of the secondary battery are significantly improved, and are suitable for high-demand energy storage application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481060A_ABST
    Figure CN119481060A_ABST
Patent Text Reader

Abstract

The invention provides a pole piece and a preparation method thereof, a battery and an energy storage device, the pole piece comprises a current collector, at least one surface of the current collector is provided with an active material layer, the active material layer comprises an active material, and a sheet-shaped porous carbon material is distributed on the particle surface of the active material. The flaky porous carbon material is formed by partially carbonizing a carbon-containing precursor material with the carbonization temperature range of 150-400 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a pole piece and a preparation method thereof, a battery and an energy storage device. Background Art

[0002] Secondary batteries (such as lithium-ion batteries) have the advantages of high energy density, low self-discharge, and light weight, and are therefore widely used in fields such as energy storage devices.

[0003] The pole pieces in secondary batteries include positive pole pieces and negative pole pieces. As the main structural part of secondary batteries, pole pieces play an important role in the performance of secondary batteries. With the improvement of people's requirements for the performance of secondary batteries, for example, the requirements for the performance of secondary batteries in wind power generation and energy storage scenarios or solar power generation and energy storage scenarios, how to reduce the resistivity of pole pieces to improve the rate performance and cycle performance of secondary batteries has become an urgent problem to be solved. Summary of the invention

[0004] In order to solve the above technical problems, the present application discloses a pole piece and a preparation method thereof, a battery and an energy storage device to reduce the resistivity of the pole piece, thereby improving the rate performance and cycle performance of the secondary battery.

[0005] In the first aspect, the present application provides a pole piece, including a current collector, at least one side of the current collector having an active material layer, the active material layer including an active material, and flaky porous carbon material distributed on the surface of the particles of the active material, the flaky porous carbon material is formed by partial carbonization of a carbon-containing precursor material with a carbonization temperature range of 150°C to 400°C.

[0006] In some embodiments of the present application, the current collector includes a negative electrode current collector. In the XRD test results of the negative electrode current collector, the texture coefficient of the crystal plane (111) is TC(111), the texture coefficient of the crystal plane (200) is TC(200), the texture coefficient of the crystal plane (220) is TC(220), 30%≤TC(111)≤45%, 30%≤TC(200)≤45%, and 10%≤TC(220)≤20%.

[0007] In some embodiments of the present application, the electrode sheet includes a negative electrode sheet, at least one side of the negative electrode sheet has a negative electrode active material layer, and the carbon content in the negative electrode active material layer is 58% to 61%.

[0008] In some embodiments of the present application, the resistivity of the negative electrode plate is 0.002Ω·m to 0.04Ω·m.

[0009] In some embodiments of the present application, the peel strength of the negative electrode sheet is 6 N / m to 16 N / m.

[0010] In some embodiments of the present application, the electrode sheet includes a positive electrode sheet, and the positive electrode sheet satisfies at least one of the following characteristics:

[0011] a) the resistivity of the positive electrode sheet is 0.1Ω·m to 0.5Ω·m;

[0012] b) The peel strength of the positive electrode sheet is 18N / m to 30N / m.

[0013] In some embodiments of the present application, the carbon-containing precursor material includes at least one of sodium alginate, chitin, chitosan and derivatives thereof, polyhydroxyalkyl alcohol esters, polyhydroxyalkanoates, polycaprolactone and polycyanoacrylate.

[0014] In a second aspect, the present application provides a method for preparing a pole piece as described in the first aspect, comprising the following steps:

[0015] Applying the electrode slurry containing the carbon-containing precursor material on at least one surface of the current collector, drying and rolling to form an active material layer, thereby obtaining a semi-finished electrode sheet;

[0016] The pole piece semi-finished product is sintered at a sintering temperature of 150° C. to 400° C. in an inert atmosphere, so that the carbon-containing precursor material is partially carbonized, and the carbonized area is transformed into a flaky porous carbon material, thereby obtaining a sintered pole piece.

[0017] In some embodiments of the present application, the heating rate of the sintering treatment is 1° C. / min to 10° C. / min, and the holding time is 1 min to 60 min.

[0018] In some embodiments of the present application, the electrode sheet semi-finished product includes a negative electrode sheet semi-finished product. Based on the mass of the active material layer in the negative electrode sheet semi-finished product, the mass percentage of the negative electrode active material is 94% to 99%, the mass percentage of the negative electrode binder is 0.5% to 4.5%, the mass percentage of the conductive agent is 0.1% to 1.5%, and the mass percentage of the carbon-containing precursor material is 0.1% to 1.5%.

[0019] In some embodiments of the present application, the current collector includes a negative electrode current collector, and the conductivity of the negative electrode current collector after the sintering treatment is increased by more than or equal to 2%.

[0020] In some embodiments of the present application, the electrode sheet semi-finished product includes a positive electrode sheet semi-finished product. Based on the mass of the active material layer in the positive electrode sheet semi-finished product, the mass percentage of the positive electrode active material is 94% to 99%, the mass percentage of the positive electrode binder is 0.5% to 5.5%, the mass percentage of the conductive agent is 0.1% to 1.5%, the mass percentage of the dispersant is 0.1% to 1.0%, and the mass percentage of the carbon-containing precursor material is 0.1% to 1.5%.

[0021] In a third aspect, the present application provides a battery, comprising the electrode described in the first aspect.

[0022] In a fourth aspect, the present application provides an energy storage device, comprising a housing and at least one battery as described in the third aspect, wherein the battery is accommodated in the housing.

[0023] In a fifth aspect, the present application provides an electrical device, comprising the energy storage device described in the fourth aspect, wherein the energy storage device supplies power to the electrical device.

[0024] Compared with the prior art, this application has at least the following beneficial effects:

[0025] The present application provides a pole piece and a preparation method thereof, a battery and an energy storage device, wherein the active material layer of the pole piece includes an active material, and a flaky porous carbon material is distributed on the surface of the particles of the active material, and the flaky porous carbon material is formed by partial carbonization of a carbon-containing precursor material having a carbonization temperature range of 150°C to 400°C, and the flaky porous carbon material has a relatively ordered nanoscale membrane sheet structure, which gives the material excellent electrical conductivity, thereby reducing the resistivity of the pole piece; and the flaky porous carbon material is distributed on the surface of the particles of the active material, which increases the conductive channel between the particles of the active material on the one hand, and reduces the direct contact between the surface of the active material particles and the electrolyte on the other hand, thereby reducing the generation of electrochemical side reactions. Under the combined effect of the above factors, the rate performance and cycle performance of the secondary battery are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 This is a scanning electron microscope (SEM) image of the surface of the active material layer of the negative electrode plate of Example 1-1 of the present application after sintering;

[0028] Figure 2A schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application;

[0029] Figure 3 A schematic diagram of the structure of an energy storage system according to an implementation scheme of the present application;

[0030] Figure 4 This is a SEM image of the surface of the active material layer of the semi-finished negative electrode sheet of Example 1-1 of the present application. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0032] In the present application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings. These terms are mainly used to better describe the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.

[0033] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.

[0034] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0035] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.

[0036] It should be noted that, in the present application, a lithium-ion battery is used as an example of a secondary battery to explain the present application, but the secondary battery of the present application is not limited to a lithium-ion battery.

[0037] In the related art, the conductive agent in the active material layer, such as acetylene black, carbon black and other point structures, is difficult to disperse evenly due to the fine particle size of the active material powder formed by the point structure; and the point-to-point contact conductive network limits the conductive effect, increasing the amount of conductive agent used; and if the proportion of the conductive agent in the electrode slurry is further increased, it is easy to cause the viscosity of the electrode slurry to exceed the standard. In addition, although carbon nanotubes, graphene and the like have good conductive effects, they are expensive and cannot be applied in large-scale, low-cost batches at present.

[0038] In view of this, the present application provides a pole piece, which includes a current collector, at least one side of the current collector has an active material layer, and the active material layer includes a granular active material, see Figure 1 , the active material particles are distributed with flaky porous carbon materials ( Figure 1 The flaky porous carbon material is formed by partial carbonization of a carbon-containing precursor material with a carbonization temperature range of 150°C to 400°C. The flaky porous carbon material has a relatively ordered nanoscale membrane structure, which gives the material excellent electrical conductivity, thereby reducing the resistivity of the pole piece; and, since the active material layer also includes a binder, the flaky porous carbon material will also be distributed in the binder, thereby connecting the conductive channels between the active material particles covered by the binder, and connecting the conductive channels between the flaky porous carbon material and the electrolyte; and, the flaky porous carbon material is distributed on the surface of the active material particles, which, on the one hand, increases the conductive channels between the active material particles, and on the other hand, reduces the direct contact between the surface of the active material particles and the electrolyte, reducing the generation of electrochemical side reactions. Under the combined effect of the above factors, the rate performance and cycle performance of lithium-ion batteries are improved.

[0039] The sheet-like porous carbon material of the present application may exist in the active material layer of the positive electrode sheet, or may exist in the active material layer of the negative electrode sheet.

[0040] In an optional embodiment, the current collector includes a negative electrode current collector, and in the X-ray diffractometer (XRD) test results of the negative electrode current collector (such as copper foil), the texture coefficient of the crystal plane (111) is TC(111), the texture coefficient of the crystal plane (200) is TC(200), and the texture coefficient of the crystal plane (220) is TC(220), wherein 30%≤TC(111)≤45%, 30%≤TC(200)≤45%, and 10%≤TC(220)≤20%. For example, TC(111) is 35%, 38%, 40% or 45%; TC(200) is 35%, 38%, 40% or 45%; and TC(220) is 10%, 13%, 15% or 20%. The texture coefficient of the negative electrode current collector is within the above range, indicating that the negative electrode current collector has undergone low-temperature sintering annealing treatment, and the proportion of its different texture coefficients has changed, while the conductivity of the negative electrode current collector after low-temperature annealing treatment is improved, which is beneficial to the improvement of the rate performance of lithium-ion batteries.

[0041] In an optional embodiment, the electrode sheet includes a negative electrode sheet, at least one side of the negative electrode sheet has a negative electrode active material layer, and the carbon content in the negative electrode active material layer is 58% to 61%, for example, the carbon content is 58%, 59%, 60% or 61%. In this way, on the one hand, a relatively high carbon content in the negative electrode active material layer is conducive to improving the conductivity of the negative electrode sheet, thereby improving the rate performance of the lithium-ion battery; on the other hand, an excessively high carbon content indicates that the proportion of carbon-containing precursors in the negative electrode active material layer is too high, thereby affecting the relative content of the binder and / or active material, which is not conducive to maintaining the peel strength of the electrode sheet, nor is it conducive to improving the specific capacity of the lithium-ion battery. Therefore, by regulating the carbon content in the negative electrode active material layer within the above range, it is beneficial to make the electrode sheet have good peel strength and the lithium-ion battery have a higher specific capacity.

[0042] In an optional embodiment, the resistivity of the negative electrode plate is 0.002Ω·m to 0.04Ω·m, for example, the resistivity is 0.002Ω·m, 0.005Ω·m, 0.01Ω·m or 0.04Ω·m, which has a lower resistivity, which is beneficial to improving the conductivity of the negative electrode plate, thereby facilitating the improvement of the rate performance of the lithium-ion battery.

[0043] In an optional embodiment, the peel strength of the negative electrode sheet is 6N / m to 16N / m, for example, the peel strength is 6N / m, 8N / m, 9N / m or 16N / m, so that the negative electrode active material layer is less likely to fall off during the cycle, which is beneficial to improving the cycle performance of the lithium-ion battery.

[0044] In an optional embodiment, the electrode sheet includes a positive electrode sheet, and the resistivity of the positive electrode sheet is 0.1Ω·m to 0.5Ω·m, for example, the resistivity is 0.1Ω·m, 0.2Ω·m, 0.3Ω·m or 0.5Ω·m. It has a lower resistivity, which is beneficial to improving the conductive properties of the positive electrode sheet, thereby facilitating the improvement of the rate performance of the lithium-ion battery.

[0045] In an optional embodiment, the pole piece includes a positive pole piece, and the peel strength of the positive pole piece is 18N / m to 30N / m, for example, the peel strength is 18N / m, 20N / m, 25N / m or 30N / m, so that the positive electrode active material layer is less likely to fall off during the cycle process, which is beneficial to improve the cycle performance of the lithium-ion battery.

[0046] In an optional embodiment, the carbon-containing precursor material includes at least one of sodium alginate, chitin, chitosan and its derivatives, polyhydroxyalkyl alcohol esters, polyhydroxyalkanoates, polycaprolactone and polycyanoacrylate. The above materials have the advantages of wide sources and low prices, which are conducive to large-scale low-cost batch applications, thereby reducing the manufacturing cost of lithium-ion batteries and are more suitable for energy storage application scenarios.

[0047] The present application provides a pole piece, which is obtained by integrally sintering a pole piece having an active material layer and a current collector of the present application. The carbon-containing precursor material in the pole piece is partially carbonized to form a flaky porous carbon material. The current collector in the pole piece is annealed, the proportion of texture coefficients of different crystal plane orientations changes, and the resistivity is significantly reduced.

[0048] The present application also provides a method for preparing a pole piece according to any of the above embodiments, comprising the following steps:

[0049] Step A, coating an electrode slurry containing a carbonaceous precursor material on at least one surface of a current collector, drying and rolling to form an active material layer, and obtaining a semi-finished electrode sheet;

[0050] Step B: sintering the electrode semi-finished product at a sintering temperature of 150° C. to 400° C. under an inert atmosphere to partially carbonize the carbon-containing precursor material and convert the carbonized area into a flaky porous carbon material to obtain a sintered electrode.

[0051] In step A, the electrode slurry can be slit-coated by a double-sided coating process, and the active material layer is formed after drying and rolling on both surfaces of the current collector; or, the electrode slurry can be slit-coated by a single-sided coating process, and the active material layer is formed after drying and rolling on one surface of the current collector. In addition, the preparation process of the electrode slurry containing the carbon-containing precursor material is as follows: the active material, binder, conductive agent, dispersant (dispersant can be added if not needed) and carbon-containing precursor material are weighed according to the designed mass ratio, and then the active material, conductive agent, dispersant and carbon-containing precursor material are first stirred evenly in a stirrer, and then the solvent and binder are added for kneading, shearing, stirring and mixing, and the slurry is evenly dispersed to obtain the electrode slurry. When the electrode slurry is a negative electrode slurry, the solid content of the negative electrode slurry is 50% to 60%, and the viscosity at 25°C is 5Pa.s to 8Pa.s. The above-mentioned solvent can be pure water or N-methylpyrrolidone (NMP).

[0052] In step B, after the sintering treatment, the pole piece is naturally cooled down. The inventors have found that when the sintering temperature is too low (for example, below 150°C), the carbonization effect of the carbon-containing precursor material is poor, resulting in the conductivity of the active material not being significantly improved, which is not conducive to reducing the resistivity of the pole piece; when the sintering temperature is too high (for example, above 400°C), the binder in the active material layer is easily carbonized, affecting the bonding effect, making the active material layer brittle or even falling off, and the current collector foil will also undergo obvious recrystallization, and the grains absorb heat and become too coarse, resulting in the current collector foil strength becoming poor and easier to break. By regulating the sintering temperature within the scope of this application, not only can the resistivity of the pole piece be reduced, but also the bonding performance of the active material layer and the strength of the current collector can be guaranteed, thereby improving the overall strength of the pole piece, which is beneficial to improving the rate performance and cycle performance of lithium-ion batteries.

[0053] The inert atmosphere of the present application may include but is not limited to argon, nitrogen, helium, etc., and its function is to prevent the current collector from being oxidized during the sintering process.

[0054] In an optional embodiment, the heating rate of the sintering treatment is 1°C / min to 10°C / min, and the holding time is 1min to 60min. For example, the heating rate is 1°C / min, 5°C / min or 10°C / min, and the holding time is 1min, 30min or 60min. By regulating the heating rate and the holding time within the above range, it is beneficial to control the carbonization effect of the carbon-containing precursor material, and the carbon-containing precursor material is partially carbonized without significantly affecting the peel strength of the pole piece, forming a flaky porous carbon material on the surface of the active material particles.

[0055] In an optional embodiment, the electrode sheet semi-finished product includes a negative electrode sheet semi-finished product, based on the mass of the active material layer in the negative electrode sheet semi-finished product, the mass percentage of the negative electrode active material is 94% to 99%, the mass percentage of the negative electrode binder is 0.5% to 4.5%, the mass percentage of the conductive agent is 0.1% to 1.5%, and the mass percentage of the carbon-containing precursor material is 0.1% to 1.5%. By regulating the content of each component in the negative electrode sheet semi-finished product within the above range, a negative electrode sheet with low resistivity can be obtained with a relatively small content of the conductive agent, which is conducive to achieving a balance between the energy density and power density of lithium-ion batteries and improving the rate performance of lithium-ion batteries.

[0056] In an optional embodiment, the current collector includes a negative electrode current collector, and the conductivity of the negative electrode current collector after sintering is increased by 2% or more. The sintering process of the present application is conducive to annealing the current collector foil, which can eliminate supersaturated point defects, and the grain boundaries of the current collector foil migrate to generate twins, and the twin grain boundary resistance is low, thereby improving the conductivity of the current collector.

[0057] In an optional embodiment, the electrode sheet semi-finished product includes a positive electrode sheet semi-finished product, based on the mass of the active material layer in the positive electrode sheet semi-finished product, the mass percentage of the positive electrode active material is 94% to 99%, the mass percentage of the positive electrode binder is 0.5% to 5.5%, the mass percentage of the conductive agent is 0.1% to 1.5%, the mass percentage of the dispersant is 0.1% to 1.0%, and the mass percentage of the carbon-containing precursor material is 0.1% to 1.5%. By regulating the content of each component in the positive electrode sheet semi-finished product within the above range, a low-resistivity positive electrode sheet can be obtained with a relatively small content of the conductive agent, which is conducive to achieving a balance between the energy density and power density of lithium-ion batteries and improving the rate performance of lithium-ion batteries.

[0058] The present application provides a method for preparing a pole piece, wherein a pole piece having an active material layer and a current collector is sintered as a whole, and the active material layer contains a carbonaceous precursor material, the carbonaceous precursor material is partially carbonized to form a flaky porous carbon material, and the current collector in the pole piece is annealed, and the resistivity is significantly reduced. When the pole piece is used in a lithium-ion battery, it is beneficial to achieve a balance between the energy density and power density of the lithium-ion battery, and improve the rate performance of the lithium-ion battery.

[0059] The present application also provides a battery, comprising the pole piece described in any of the above embodiments.

[0060] In the present application, the negative electrode active material layer can be arranged on one surface or two surfaces along the thickness direction of the negative electrode current collector. In the present application, the negative electrode active material layer is arranged on the surface of the negative electrode current collector, that is, the negative electrode active material layer can be arranged in a partial area of ​​one surface of the negative electrode current collector, or it can be arranged in the entire area of ​​one surface of the negative electrode current collector. The present application has no special restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it can include but is not limited to copper foil, copper alloy foil, etc. In the present application, there is no special restriction on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness is 5μm to 10μm, specifically, it can be 5μm, 6μm, 7μm, 8μm, 9μm or 10μm. The total thickness of both sides of the negative electrode active material layer of the present application can be 130μm to 200μm, and the surface density is 300g / m 2 ~400g / m 2 .

[0061] In the present application, the negative electrode active material layer includes a negative electrode active material, wherein the negative electrode active material is not particularly limited as long as the purpose of the present application can be achieved, for example, it may include at least one of natural graphite, artificial graphite, intermediate phase microcarbon beads, hard carbon and soft carbon; the negative electrode active material layer also includes a negative electrode binder, and the negative electrode binder includes at least one of polyacrylic acid, sodium polyacrylate, polyvinyl alcohol, styrene-butadiene rubber (SBR), carboxymethyl cellulose (or its sodium salt) (CMC) and polymethacrylic acid; the negative electrode active material layer also includes a conductive agent, and the conductive agent includes at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon nanotubes, graphene and carbon nanofibers.

[0062] In the present application, the positive electrode active material layer can be arranged on one surface in the thickness direction of the positive electrode current collector, or on both surfaces in the thickness direction of the positive electrode current collector. In the present application, the positive electrode active material layer is arranged on the surface of the positive electrode current collector, that is, the positive electrode active material layer can be arranged in a partial area of ​​one surface of the positive electrode current collector, or in the entire area of ​​one surface of the positive electrode current collector. In the present application, there is no special restriction on the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, it can include but is not limited to aluminum foil, aluminum alloy foil, etc. In the present application, there is no special restriction on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 7μm to 13μm, specifically, it can be 7μm, 8μm, 9μm, 10μm, 11μm, 12μm or 13μm. The total thickness of both sides of the positive electrode active material layer of the present application can be 50μm to 220μm, and the surface density is 200g / m 2 ~400g / m 2 .

[0063] In the present application, the positive electrode active material layer includes a positive electrode active material, wherein the positive electrode active material is not particularly limited as long as the purpose of the present application can be achieved, for example, it may include at least one of lithium iron phosphate, ternary material, lithium titanate, lithium cobaltate and lithium manganate; the positive electrode active material layer also includes a positive electrode binder, and the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene; the positive electrode active material layer also includes a conductive agent, and the conductive agent includes at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon nanotubes, graphene and carbon nanofibers; the positive electrode active material layer also includes a dispersant, and the dispersant includes at least one of polyacrylic acid, polyvinyl pyrrolidone and polyethylene glycol.

[0064] The sintering equipment of the present application may include but is not limited to vacuum sintering furnace, annealing furnace, quenching furnace, tempering furnace, carburizing furnace and other equipment.

[0065] The lithium-ion battery of the present application also includes a diaphragm. The present application has no particular restrictions on the diaphragm, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected.

[0066] The battery of the present application also includes an electrolyte. The present application has no particular restrictions on the electrolyte, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl propionate (EP), propyl propionate (PP), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate (VC) or fluoroethylene carbonate (FEC) is mixed in a certain mass ratio or volume ratio to obtain a non-aqueous organic solvent, and then a lithium salt is added to dissolve and mix evenly. The present application has no restrictions on the type of lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include LiPF 6 , LiBF 4 、LiAsF 6 、LiClO 4 、LiB(C 6 H 5 ) 4 、LiCH 3 SO 3 、LiCF 3 SO 3 、LiN(SO 2 CF 3) 2 、LiC(SO 2 CF 3 ) 3 、LiSiF 6 At least one of lithium bis(oxalato)borate (LiBOB) or lithium difluoroborate. The present application has no particular limitation on the concentration of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, the concentration of the lithium salt is 1.0 mol / L to 2.0 mol / L.

[0067] The battery of the present application also includes a shell, and the present application has no particular limitation on the shell, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the shell may include an aluminum-plastic film.

[0068] The present application does not particularly limit the preparation method of the battery, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the battery includes but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain a bare cell with a wound structure, placing the bare cell in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a battery.

[0069] The present application also provides an energy storage device, including a housing and at least one battery in any of the above embodiments, wherein the battery is contained in the housing. The energy storage device having the battery has excellent performance, which is beneficial to the use of the energy storage device. By containing the battery in the housing, the fixation and protection of the battery can be increased, thereby improving the service life of the energy storage device. It is understandable that the energy storage device may have one or more batteries, and when the energy storage device contains multiple batteries, the multiple batteries may be connected in at least one of parallel and series connection.

[0070] The present application also provides an electrical device, including the energy storage device in the above-mentioned implementation scheme, which is conducive to improving the product competitiveness and performance of the electrical device. In an optional implementation scheme, the electrical device includes an electrical device body, and the energy storage device is used to supply power to the electrical device body. In an optional implementation scheme, the electrical device body includes a positive electrode of the device and a negative electrode of the device, the positive electrode plate of the battery in the energy storage device is used to electrically connect to the positive electrode of the device body of the electrical device, and the negative electrode plate of the battery in the energy storage device is used to electrically connect to the negative electrode of the device body of the electrical device, so as to supply power to the electrical device.

[0071] The electrical equipment of the present application may include but is not limited to: containers, household energy storage systems, battery vehicles, electric vehicles, ships, spacecraft, electric toys and electric tools, etc., wherein spacecrafts include airplanes, rockets, space shuttles and spacecrafts, etc., electric toys include fixed or mobile electric toys, such as electric car toys, electric ship toys and electric airplane toys, etc., and electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers.

[0072] See also Figure 2 , Figure 2 This is a schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application, and the present application Figure 2 The implementation plan is described using a household energy storage scenario in user-side energy storage as an example, but the energy storage device of the present application is not limited to the household energy storage scenario.

[0073] The present application provides a household energy storage system, which includes an energy conversion device 2 (photovoltaic panel), a first user load 3 (street lamp), a second user load 4 (such as air conditioner and other household appliances), and an energy storage device 1. The energy storage device 1 is a small energy storage box that can be mounted on an outdoor wall by wall hanging. Specifically, the photovoltaic panel can convert solar energy into electrical energy during the period of low electricity prices. The energy storage device 1 is used to store the electrical energy and supply it to street lamps and household appliances for use during the peak electricity prices, or to supply power when the power grid is out of power / power outage.

[0074] See also Figure 3 , Figure 3 This is a schematic diagram of the structure of an energy storage system 400 according to an implementation scheme of the present application, and the present application Figure 3 The implementation plan is described using the shared energy storage scenario on the generation / distribution side as an example, and the energy storage device 1 of the present application is not limited to the energy storage scenario on the generation / distribution side.

[0075] The present application provides an energy storage system 400, which includes: a high-voltage cable 410, a first electric energy conversion device 420, a second electric energy conversion device 430 and an energy storage device 1 provided in the present application. In the case of power generation, the first electric energy conversion device 420 and the second electric energy conversion device 430 are used to convert other forms of energy into electric energy, which are connected to the high-voltage cable 410 and supplied to the power distribution network for use. When the power load is low and the first electric energy conversion device 420 and the second electric energy conversion device 430 generate excess power, the excess power is stored in the energy storage device 1, thereby reducing the wind and solar power abandonment rates and improving the problem of new energy power generation and consumption. When the power load is high, the power grid issues an instruction to transmit the power stored in the energy storage device 1 in conjunction with the high-voltage cable 410 in a grid-connected mode to the power consumption side, thereby providing peak shaving, frequency regulation, standby and other services for the power grid operation, giving full play to the peak shaving role of the power grid, promoting peak shaving and valley filling of the power grid, and alleviating the power supply pressure of the power grid.

[0076] Optionally, the first electric energy conversion device 420 and the second electric energy conversion device 430 can convert at least one of solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.

[0077] The number of energy storage devices 1 can be multiple, and multiple energy storage devices 1 are connected in series or in parallel. Multiple energy storage devices 1 are supported and electrically connected by isolation plates (not shown). In this embodiment, "multiple" refers to two or more. An energy storage box can also be provided outside the energy storage device 1 to accommodate the energy storage device 1.

[0078] Optionally, the energy storage device 1 may include but is not limited to a battery module, a battery pack, a battery system, etc. Among them, the battery module may be a battery module formed by connecting multiple batteries of the present application in series / parallel, the battery pack may include multiple batteries of the present application, and the battery system may be a charging and discharging system including the battery or battery pack of the present application.

[0079] The actual application form of the energy storage device 1 provided in the embodiment of the present application may be, but is not limited to, the listed products, and may also be other application forms. The embodiment of the present application does not strictly limit the application form of the energy storage device 1. The embodiment of the present application only takes the energy storage device 1 as a multi-core battery as an example for explanation. When the energy storage device 1 is a single battery, the energy storage device 1 may be at least one of a cylindrical battery, a square battery, and the like.

[0080] Example

[0081] Hereinafter, the embodiments of the present application will be described in more detail with reference to preparation examples, examples and comparative examples. Various tests and evaluations were performed according to the following methods.

[0082] Example 1-1

[0083] <Preparation of negative electrode sheet>

[0084] According to the mass ratio of 96.5:1.6:0.8:1:0.1, artificial graphite as negative electrode active material, SBR as negative electrode binder, CMC as negative electrode binder, conductive carbon black (Super-P) as conductive agent and sodium alginate as carbon-containing precursor material (wherein the mass ratio of SBR to CMC is 2:1) are weighed. First, artificial graphite, CMC, conductive carbon black and sodium alginate are uniformly stirred in a double planetary stirrer, and then deionized water and SBR are added for kneading, shearing and stirring to mix, and the slurry is uniformly dispersed to obtain a negative electrode slurry with a solid content of 60% and a viscosity of 6 Pa.s at 25°C; the obtained negative electrode slurry is double-sidedly coated on a Cu foil with a thickness of 6 μm through a slit extruder, and then rolled and compacted after drying to obtain a negative electrode sheet semi-finished product, and the single-sided thickness of the negative electrode active material layer is 70 μm, and the surface density is 350 g / m 2 ; Place the negative electrode semi-finished product in a vacuum sintering furnace, add argon atmosphere protection, and perform sintering treatment. The sintering temperature is 275°C, the heating rate is 4°C / min, and the holding time is 30min. Take it out after cooling. After the processes of striping and cutting, the negative electrode is obtained.

[0085] <Preparation of positive electrode sheet>

[0086] The positive electrode active material lithium iron phosphate (LiFePO 4 ), conductive carbon black (Super-P), and positive electrode binder PVDF are mixed in a mass ratio of 97:1:2; then N-methylpyrrolidone (NMP) is added as a solvent and stirred evenly to prepare a positive electrode slurry with a solid content of 60wt%, and then the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 11μm, and dried at 85℃, and then the above steps are repeated on the other surface of the positive electrode sheet, and after rolling, a positive electrode sheet with a positive electrode active material layer coated on both sides is obtained. The single-sided thickness of the positive electrode active material layer is 100μm.

[0087] <Preparation of Electrolyte>

[0088] Ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 1:1:1, dissolved, and stirred thoroughly, and then placed in an environment of 5°C or less for 12 hours, and then lithium hexafluorophosphate (LiPF 6 ), and then mixed evenly to obtain an electrolyte. Among them, LiPF 6 The molar concentration in the electrolyte is 1.0 mol / L.

[0089] <Preparation of lithium-ion batteries>

[0090] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, with the separator placed between the positive electrode and the negative electrode to play an isolating role, and wound to obtain a bare cell. The bare cell is placed in an aluminum-plastic film packaging bag, and after vacuum drying, the electrolyte is injected, and a soft-pack lithium-ion battery with a capacity of 3.55Ah is obtained through vacuum packaging, standing, and formation processes.

[0091] Example 1-2 to Example 1-4

[0092] Except that in <Preparation of Negative Electrode Plate>, the content of the carbon-containing precursor material (sodium alginate) is regulated according to Table 1, the rest is the same as Example 1-1.

[0093] Example 2-1 to Example 2-3

[0094] Except that the sintering temperature and holding time of the sintering treatment are regulated according to Table 2 in <Preparation of Negative Electrode Plate>, the rest is the same as Example 1-2.

[0095] Example 3-1 to Example 3-3

[0096] Except that the type of carbon-containing precursor material is regulated according to Table 3 in <Preparation of Negative Electrode Plate>, the rest is the same as Example 1-2.

[0097] Comparative Example 1

[0098] Except that no carbon-containing precursor material is added and no sintering treatment is performed in the preparation of the negative electrode sheet, the rest is the same as Example 1-1. The preparation process of the negative electrode sheet is as follows:

[0099] The negative electrode active material artificial graphite, negative electrode binder SBR, negative electrode binder CMC and conductive carbon black (Super-P) were mixed in a mass ratio of 96.5:1.67:0.83:1 (wherein the mass ratio of SBR to CMC was 2:1), deionized water was added, and a negative electrode slurry with a solid content of 60wt% was prepared, and stirred evenly. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, dried at 85°C, and then the above steps were repeated on the other surface of the negative electrode sheet. After rolling, a negative electrode sheet with a negative electrode active material layer coated on both sides was obtained, and the single-side thickness of the negative electrode active material layer was 70μm.

[0100] Comparative Example 2

[0101] Except that no carbon-containing precursor material is added in the preparation of the negative electrode sheet, the rest is the same as that of Example 1-1.

[0102] Comparative Example 3

[0103] Except that in <Preparation of Negative Electrode Plate>, the content of the carbon-containing precursor material (sodium alginate) is regulated according to Table 1, the rest is the same as Example 1-1.

[0104] Test methods and equipment

[0105] Current collector texture coefficient test:

[0106] According to the standards "GB / T 37983-2019 X-ray diffractometer rotation orientation test method for crystal materials" and "GB / T30904-2014 X-ray diffraction method for crystal structure analysis of inorganic chemical products", the current collector (such as copper foil) is tested by XRD, and the texture coefficient TC (Texture Coefficient) of different crystal planes (hkl) is calculated from the crystal plane diffraction peak intensity of the XRD spectrum, and the texture coefficient TC of typical crystal planes (111), (200), and (220) of the current collector (such as copper foil) is obtained. (hkl) , the calculation formula is as follows:

[0107]

[0108] In the formula, I (hkl) is the diffraction peak intensity of the copper foil sample (hkl) crystal plane, I 0(hkl) is the diffraction peak intensity of the standard copper powder (hkl) crystal surface. TC (hkl) The larger the value, the higher the degree of preferred orientation of the crystal plane.

[0109] Carbon content test in active material layer:

[0110] Referring to the standard "GB / T 20123-2006 Determination of total carbon and sulfur content of steel - Infrared absorption method after combustion in a high-frequency induction furnace (conventional method)", a carbon-sulfur analyzer was used to test the carbon content in the active material layer of the dried electrode.

[0111] Electrode resistivity test:

[0112] The resistivity test of the electrode was carried out according to the standard "GB / T 1410-2006 Test method for volume resistivity and surface resistivity of solid insulating materials": the electrode was cut into samples with a size of 60mm*80mm, and then the samples were placed on the test hole of the electrode resistance meter, the protective door was closed, the pressure was maintained at 0.5MPa, the pressure was maintained for 15s, 5 samples were tested, and then the average value was taken to obtain the resistivity of the electrode in Ω·m.

[0113] Pole peel strength test:

[0114] The pole piece was tested for peel strength according to the standard GB / T 2792-2014 Test method for peel strength of adhesive tape. The pole piece was cut into samples with a size of 25mm*250mm, and then the samples were adhered to a steel plate with 3M double-sided tape. After rolling with a roller for 3 times, the steel plate was fixed in the middle of the clamp of the tensile testing machine, and then the tensile testing machine was used to peel the pole piece and the steel plate along the 180° direction at a speed of 50mm / min. The test distance was up to 80mm, and 5 samples were tested. The average value was taken, which was the peel strength of the pole piece in N / m.

[0115] Negative electrode current collector conductivity test:

[0116] The volume resistivity ρ and conductivity C of the negative electrode current collector were tested and calculated with reference to the standard "GB / T 351-2019 Metal Material Resistivity Measurement Method". The negative electrode current collector was cut into 300mm*25mm samples in the width direction*machine direction (TD*MD) direction. The two ends of the negative electrode current collector in the TD direction were clamped with the resistance meter test end to obtain the resistance value R of the sample. The ambient temperature was 20°C and the current was 1.03A. Each negative electrode current collector sample was tested three times and the average value was taken. The volume resistivity ρ and conductivity C were calculated by the following formula:

[0117] ρ=(R×A) / L(1)

[0118] C=0.017241 / ρ×100%(2)

[0119] In formula (1), ρ is the volume resistivity of the sample, in Ω·m; R is the resistance value of the sample, in Ω; A is the cross-sectional area of ​​the sample, in m 2 ; L is the gauge length of the sample, in m.

[0120] In formula (2), C is the conductivity of the sample, in %; ρ is the volume resistivity of the sample, in Ω·m; the international annealed copper standard adopts a density of 8.89 g / cm 2 The annealed copper wire with a length of 1 m, a mass of 1 g, and a resistance of 0.153280 Ω was used as a reference. At a temperature of 20°C, the resistivity of the annealed copper wire was 0.017241 Ω·m, which was determined to be 100% IACS.

[0121] The conductivity of the unsintered copper foil is recorded as C 0 The conductivity of the sintered copper foil is recorded as C 1 , then the increase in the conductivity of copper foil is: (C 1 -C 0 ) / C 0 ×100%.

[0122] Cycle performance test:

[0123] The test temperature is 25°C. The lithium-ion battery is charged to 3.65V at a constant current of 0.5P, and then discharged to 2.5V at a constant power of 0.5P; this is one charge and discharge cycle. In this way, the capacity retention rate of the battery after 120 cycles is calculated. The capacity retention rate of the lithium-ion battery after 120 cycles (%) = the discharge capacity of the 120th cycle / the discharge capacity of the first cycle × 100%.

[0124] Rate performance test:

[0125] Referring to the standards "GB / T 42161-2022 Test method for first discharge specific capacity and first charge and discharge efficiency of lithium iron phosphate electrochemical performance test" and "GB / T 44027.1-2024 Carbon material determination method Part 1: Determination of first discharge specific capacity, first coulombic efficiency, and retention rate of discharge capacity at different rates", the lithium-ion battery was tested for its first efficiency and specific capacity, and the discharge capacity retention rate at 1 rate (C), 2C, and 3C was calculated.

[0126] Table 1 Parameters of Examples 1-1 to 1-4 and Comparative Examples 1 to 3

[0127]

[0128]

[0129] Table 2 Parameters of Examples 1-2, 2-1 to 2-3, and Comparative Examples 1 to 2

[0130]

[0131] In Table 2, “ / ” indicates that there is no relevant preparation parameter.

[0132] Table 3 Related parameters of Example 1-2, Example 3-1 to Example 3-3

[0133]

[0134] Table 4 Performance data of lithium ion batteries in various embodiments and comparative examples

[0135]

[0136]

[0137] Combined with Table 1, it can be seen from Example 1-1 and Comparative Example 1 that compared with Comparative Example 1 which was not sintered, the peel strength of the pole piece of Example 1-1 of the present application did not change much, indicating that the sintering treatment system of the present application has basically no effect on the peel strength of the pole piece; it can be seen from Example 1-1 and Comparative Example 2 to Comparative Example 3 that when no carbon-containing precursor material is added (such as Comparative Example 2), the relative content of carbon in the negative electrode active material layer is low after sintering, which is not conducive to improving the conductive performance of the pole piece; when the addition amount of the carbon-containing precursor material is too high (such as Comparative Example 3), the sintering treatment has a greater impact on the peel strength of the pole piece, indicating that the addition amount of the carbon-containing precursor material should not be too little or too much. By adjusting the addition amount of the carbon-containing precursor material within the scope of the present application, it is beneficial to improve the conductive performance of the pole piece while maintaining good peel strength of the pole piece.

[0138] Combined with Table 2, it can be seen from Examples 1-2, 2-1 to 2-3, and Comparative Examples 1 to 2 that, on the basis of adding the carbon-containing precursor material of the present application to the electrode, by regulating the sintering temperature and the holding time of the sintering treatment within the scope of the present application, it is beneficial to obtain an electrode with a lower resistivity.

[0139] The type of carbon-containing precursor material usually also affects the performance of the electrode. Combined with Table 3, it can be seen from Examples 1-2 and 3-1 to 3-3 that by selecting the type of carbon-containing precursor material of the present application and combining it with the sintering system of the present application, it is beneficial to obtain a electrode with good peel strength and low resistivity, which is beneficial to improving the rate performance and cycle performance of lithium-ion batteries.

[0140] Combined with Table 4, it can be seen from Examples 1-1 to 3-3 and Comparative Examples 1 to 3 that, on the basis of adding a carbon-containing precursor material to the electrode, by adjusting the sintering temperature and the holding time of the sintering treatment within the scope of the present application, the discharge performance of the lithium-ion battery at different rates is improved, and the cycle performance is improved. It can be seen that the electrode of the present application is beneficial to improving the rate performance and cycle performance of the lithium-ion battery.

[0141] Figure 1 This is a SEM image of the surface of the active material layer of the negative electrode plate of Example 1-1 of the present application after sintering; Figure 4 This is a SEM image of the active material layer surface of the semi-finished negative electrode sheet of Example 1-1 of the present application. Figure 1 It can be seen that after sintering, the surface of the active material particles is distributed with flaky porous carbon materials ( Figure 1 Bright white flakes); but from Figure 4 It can be seen that there is no obvious attachment on the particle surface of the active material before sintering.

[0142] The above is a detailed introduction to a pole piece and its preparation method, a battery and an energy storage device disclosed in the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core inventions of the embodiments of the present application. At the same time, for those skilled in the art, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A pole piece, characterized in that: It includes a current collector, at least one side of which has an active material layer, the active material layer includes active materials, and the surface of the active material particles is distributed with flaky porous carbon materials, which are formed by partial carbonization of a carbon-containing precursor material with a carbonization temperature range of 150°C to 400°C.

2. The pole piece according to claim 1, characterized in that: The current collector includes a negative electrode current collector. In an XRD test result of the negative electrode current collector, the texture coefficient of the crystal plane (111) is TC(111), the texture coefficient of the crystal plane (200) is TC(200), the texture coefficient of the crystal plane (220) is TC(220), 30%≤TC(111)≤45%, 30%≤TC(200)≤45%, and 10%≤TC(220)≤20%.

3. The pole piece according to claim 1, characterized in that: The pole piece comprises a negative pole piece, at least one side of the negative pole piece has a negative active material layer, and the carbon content in the negative active material layer is 58% to 61%.

4. The pole piece according to claim 3, characterized in that: The resistivity of the negative electrode plate is 0.002Ω·m to 0.04Ω·m.

5. The pole piece according to claim 3, characterized in that: The peel strength of the negative electrode sheet is 6N / m to 16N / m.

6. The pole piece according to claim 1, characterized in that: The electrode sheet includes a positive electrode sheet, and the positive electrode sheet satisfies at least one of the following characteristics: a) the resistivity of the positive electrode sheet is 0.1Ω·m to 0.5Ω·m; b) The peel strength of the positive electrode sheet is 18N / m to 30N / m.

7. The pole piece according to any one of claims 1 to 6, characterized in that: The carbon-containing precursor material includes at least one of sodium alginate, chitin, chitosan and derivatives thereof, polyhydroxyalkyl alcohol esters, polyhydroxyalkanoates, polycaprolactone and polycyanoacrylate.

8. A method for preparing a pole piece according to any one of claims 1 to 7, characterized in that: The following steps are involved: Applying the electrode slurry containing the carbon-containing precursor material on at least one surface of the current collector, drying and rolling to form an active material layer, thereby obtaining a semi-finished electrode sheet; The pole piece semi-finished product is sintered at a sintering temperature of 150° C. to 400° C. in an inert atmosphere, so that the carbon-containing precursor material is partially carbonized, and the carbonized area is transformed into a flaky porous carbon material, thereby obtaining a sintered pole piece.

9. The preparation method according to claim 8, characterized in that: The heating rate of the sintering process is 1°C / min to 10°C / min, and the heat preservation time is 1min to 60min.

10. The preparation method according to claim 8, characterized in that: The electrode sheet semi-finished product includes a negative electrode sheet semi-finished product. Based on the mass of the active material layer in the negative electrode sheet semi-finished product, the mass percentage of the negative electrode active material is 94% to 99%, the mass percentage of the negative electrode binder is 0.5% to 4.5%, the mass percentage of the conductive agent is 0.1% to 1.5%, and the mass percentage of the carbon-containing precursor material is 0.1% to 1.5%.

11. The preparation method according to claim 8, characterized in that: The current collector includes a negative electrode current collector, and the conductivity of the negative electrode current collector is increased by more than or equal to 2% after the sintering process.

12. The preparation method according to claim 8, characterized in that: The electrode sheet semi-finished product includes a positive electrode sheet semi-finished product. Based on the mass of the active material layer in the positive electrode sheet semi-finished product, the mass percentage of the positive electrode active material is 94% to 99%, the mass percentage of the positive electrode binder is 0.5% to 5.5%, the mass percentage of the conductive agent is 0.1% to 1.5%, the mass percentage of the dispersant is 0.1% to 1.0%, and the mass percentage of the carbon-containing precursor material is 0.1% to 1.5%.

13. A battery, characterized in that: A pole piece comprising any one of claims 1 to 7.

14. An energy storage device, characterized in that: The invention comprises a casing and at least one battery according to claim 13, wherein the battery is accommodated in the casing.

15. An electrical equipment, characterized in that: It includes the energy storage device as described in claim 14, and the energy storage device supplies power to the electrical equipment.